Health check: The NHS and market reforms - Kristian Niemietz (Institute of Economic Affairs (IEA), 2014)
Since the early 2000s, the NHS has improved according to most measures of quality and performance. Survival rates for major diseases have increased, waiting lists have been shortened, and the prevalence of hospital infections has been reduced.This improvement has come from a very low base so that the performance of the NHS is still poor in international terms. For example, the UK ranks 20th out of 24 developed countries for cancer survival and 19th out of 23 for mortality amenable to healthcare. In league tables, the UK consistently ranks close to the post-communist countries of Central and Eastern Europe rather than to Western European countries. If the UK drew level with the 10th best-performing country in terms of mortality amenable to healthcare (Spain), at least 16 unnecessary deaths for every 100,000 inhabitants could be avoided each year - i.e. a total of about 10,000 deaths.The recent Commonwealth Fund study, which ranked the NHS well, has its merits, but it is structurally designed to favour an NHSstyle model of healthcare. The study's limitations are perhaps best, albeit unintentionally, captured by The Guardian's coverage of the report which stated: 'The only serious black mark against the NHS was its poor record on keeping people alive.'The UK comes 24th out of 30 high- and upper/middle-income countries for efficiency of the healthcare system. If the UK reached the efficiency level of the 5th best-performing country (Japan), life expectancy in the UK could be increased by more than two years without any additional healthcare spending and without people adopting healthier lifestyles.The reforms of the early 21st century gave well-performing hospitals more independence and introduced competition through a 'payment by results' formula. These reforms improved the service but they did not go far enough and have since stalled.The introduction of patient choice did lead patients to discriminate in favour of hospitals that had a better record. For example, postreform, a given increase in mortality after heart bypass operations led to a loss of market share for a hospital that was ten times greater than would have happened pre-reform.Scotland did not pursue the same healthcare reforms as England. The evidence shows that Scotland spends more per capita than England; it has larger numbers of hospital, dental, nursing, midwifery, health visiting, hospital management and support staff; and it has higher numbers of hospital beds and inpatient admissions. At the same time, Scotland has longer waiting times for inpatient and outpatient appointments, and longer ambulance response times. Scotland fares worse on outcome measures across the board.The intention of the reforms of the 2000s was that almost all healthcare spending would be channelled through the payment by results scheme and that the vast majority of hospitals would be Foundation Trusts. This has not materialised and the reforms need to be reinvigorated.Although non-NHS providers now account for around 9 per cent of the secondary care budget this still comes nowhere near the level of provider plurality observed in Continental European systems. For example, in Germany, the voluntary not-for-profit sector accounts for more than a third of all hospital beds, and the private for-profit sector for almost a fifth. The private sector also accounts for 38 per cent of all hospital beds in France and 30 per cent in Austria.As well as reinvigorating the reform programme of the early 21st century, in order to promote greater efficiency and quality of care, a number of second generation reforms are required:- Patients should be able to choose between different primary care providers and commissioners. They should be able to do this not just on the basis of where they live. Instead, they may, for example, choose a chain which runs branches near their place of work, or an 'identity group' based on a civil society or religious organisation. There is evidence that this approach will improve care.- Care commissioners and primary care providers should be able to vertically integrate with secondary and tertiary care providers such as hospitals.- Hospitals and other provider organisations must be allowed to go bankrupt.- Ultimately, the health service should allow complete freedom of choice so that people can choose private providers and private commissioners without restraint at all stages of healthcare. A funding system will be needed that compensates providers and commissioners according to the costs and risks that apply to different types of patients in order to prevent 'cherry picking'. Such mechanisms have long been used in other countries, and could easily be transferred to the UK.
Keywords: 330